2015
DOI: 10.2310/7290.2015.00026
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of Steroid Hormone Receptor Expression

Abstract: Steroid hormone receptor (SHR) expression and changes in SHR expression compared to basal levels, whether upregulated, downregulated, or mutated, form a distinguishing feature of some breast, ovarian, and prostate cancers. These receptors act to induce tumor proliferation. In the imaging context, total expression together with modulation of expression can yield predictive and prognostic information. Currently, biopsy for histologic assessment of SHR expression is routine for breast and prostate cancer; however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…In a retrospective study of 46 patients with histologically confirmed invasive breast cancer reported by Yang et al, the optimal 18 F-fluoroestradiol threshold was 1.21 for SUV mean and 1.82 for SUV max (8). Thus, including previously published data, optimal 18 F-fluoroestradiol SUV max thresholds for distinguishing between ER-positive and ER-negative lesions ranged from 1.5 to 2.0 (1)(2)(3)(4)6).…”
Section: Assessment Of Er Statusmentioning
confidence: 86%
See 2 more Smart Citations
“…In a retrospective study of 46 patients with histologically confirmed invasive breast cancer reported by Yang et al, the optimal 18 F-fluoroestradiol threshold was 1.21 for SUV mean and 1.82 for SUV max (8). Thus, including previously published data, optimal 18 F-fluoroestradiol SUV max thresholds for distinguishing between ER-positive and ER-negative lesions ranged from 1.5 to 2.0 (1)(2)(3)(4)6).…”
Section: Assessment Of Er Statusmentioning
confidence: 86%
“…The study highlighted the potential for 18 F-fluoroestradiol imaging to identify patients with acquired endocrine resistance who are unlikely to benefit from estradiol therapy indicated by poor 18 F-fluoroestradiol uptake. This study adds to landmark studies from Washington University and the University of Washington, which demonstrated a predictive value of 18 F-fluoroestradiol imaging for endocrine therapy benefit (1)(2)(3)(4).…”
Section: Predicting Endocrine Therapy Responsementioning
confidence: 90%
See 1 more Smart Citation
“…The biodistribution of some radioiodinated nonsteroidal estrogens also looks very promising [ 56 ], and some work has been done to advance these and related agents for both imaging and targeted in vivo radiotherapy in preclinical breast cancer models [ 57 , 58 ]. Note is made of other recent reviews covering the development of PET imaging agents for ER [ 47 , 59 ].…”
Section: Fes a Pet Imaging Agent For Estrogen Receptors In Breastmentioning
confidence: 99%
“…The use of the ER-targeted radioligand, 16α- involving primary and metastatic breast cancer. [8][9][10][11][12][13][14][15][16][17][18] Further integration of […”
Section: Introductionmentioning
confidence: 99%